Primer diakavstike - Razpet, Marko (Obzornik za matematiko in fiziko, 2009)
A diacaustic curve obtained by fraction of parallel rays of light on a half circle is discussed.
Keywords: diakavstika; geometrija; lom svetlobe; ravninske krivulje